2019
DOI: 10.1097/ta.0000000000002288
|View full text |Cite
|
Sign up to set email alerts
|

Better understanding the utilization of damage control laparotomy: A multi-institutional quality improvement project

Abstract: Background: Rates of damage control laparotomy (DCL) vary widely and consensus on appropriate indications does not exist. The purposes of this multi-center quality improvement (QI) project were to decrease the use of DCL and to identify indications where consensus exists. Methods: In 2016, six US Level 1 trauma centers performed a year-long, QI project utilizing a single QI tool: audit and feedback. Each emergent trauma laparotomy was prospectively reviewed. DCL cases were adjudicated based upon majority vote … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…In this study, only 33% of the patients who underwent DC laparotomy were acidotic, 43% hypothermic, and 48% coagulopathic on arrival at the ICU after operation [1,6,24,39]. Although the ideal rate of use of DC during emergent laparotomy is presently unknown, it was estimated in one cohort study to range between 19% and 27% across six American, level-1 trauma centers [40]. Some evidence suggests that overuse of DC laparotomy may be associated with increased morbidity and mortality [3,4,18,19,39,41].…”
Section: Vascular Damage Control Interventionsmentioning
confidence: 80%
“…In this study, only 33% of the patients who underwent DC laparotomy were acidotic, 43% hypothermic, and 48% coagulopathic on arrival at the ICU after operation [1,6,24,39]. Although the ideal rate of use of DC during emergent laparotomy is presently unknown, it was estimated in one cohort study to range between 19% and 27% across six American, level-1 trauma centers [40]. Some evidence suggests that overuse of DC laparotomy may be associated with increased morbidity and mortality [3,4,18,19,39,41].…”
Section: Vascular Damage Control Interventionsmentioning
confidence: 80%
“…These same indications may be appropriate for a larger, multicenter randomized trial DCL. 3 Second, social media allowed for efficient community consultation and public notification (both required to obtain an EFIC) in order to obtain greater reach at lesser cost than methods used in prior RCTs at our institution. 12 18-20 Lastly, we augmented our statistical approach with Bayesian analyses to avoid the pervasive misinterpretation of frequentist analyses.…”
Section: Discussionmentioning
confidence: 99%
“… 1 2 As comfort with the open abdomen has increased, indications for DCL have gradually broadened and its use has reached upward of 40% of all trauma laparotomies at some centers. 3 4 However, when used liberally, DCL may result in more risks than benefits, as several studies from trauma centers across the country have reported increased complications associated with the open abdomen resulting from DCL. 5–7 …”
Section: Introductionmentioning
confidence: 99%
“…DCL has gradually become an accepted strategy for non-trauma abdominal emergencies such as acute mesenteric ischemia and bowel perforation [7][8][9][10][11][12][13][14][15][16][17][18]. DCL has been associated with increased hospital length of stay (LOS)and resource utilization, although these findings may actually represent survival or selection bias as there are no randomized controlled trials in this area [19,20]. In the trauma population, DCL-associated complications include wound infections, enterocutaneous or entero-atmospheric fistula (ECF/EAF), intra-abdominal sepsis (IAS), and mortality [18,19,21].…”
Section: Introductionmentioning
confidence: 99%
“…DCL has been associated with increased hospital length of stay (LOS)and resource utilization, although these findings may actually represent survival or selection bias as there are no randomized controlled trials in this area [19,20]. In the trauma population, DCL-associated complications include wound infections, enterocutaneous or entero-atmospheric fistula (ECF/EAF), intra-abdominal sepsis (IAS), and mortality [18,19,21]. ECF are associated with increased morbidity and mortality, as they can lead to many complications, including fluid loss, electrolyte abnormalities, complex wound care issues, malnutrition, and increased ICU and hospital LOS [22].…”
Section: Introductionmentioning
confidence: 99%